BIOLOGICAL END ECOLOGICAL PROPERTIES OF OIL PLANTS - Gafarova Saida Muxammedjonovna; Usmonova Gulshod Ibrohimovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article delves into the biological and ecological characteristics of oilseed crops such as sunflower, olives, soybeans, and cotton, elucidating their multifaceted utility within the national economy and medicinal applications.